COMPARISON OF MILL PULVERIZER GEARBOX VIBRATION EVALUATION USING ISO 10816-3:2009 AND ISO 20816-9:2020 - Andi Kurniawan; Rivi Vedianto (Universitas Muhammadiyah Semarang, 2023)
Mill pulverizer is an important equipment in coal power plant that must be maintained for its reliability. Sudden damage of mill pulverizer can cause economic losses for power plant. Therefore, vibration assessment is carried out routinely to determine its condition status. Previously, ISO 10816-3:2009 was used as reference in vibration assessment of Mill Pulverizer gearbox. However, recently there is ISO 20816-9:2020 which is intended for the evaluation of gear vibration. This study experiment assessed the vibration of mill pulverizer based on ISO 10816-3:2009 and ISO 20816-9:2020. The results indicate that these two standards produces different vibration severity statuses. Verification of the machine's vibration severity status is carried out by analyzing the vibration spectrum data.